Aplicación de una auditoria integral a la empresa florícola Sanbel Flowers cia. ltda. ubicada en la parroquia Alaquez cantón Latacunga provincia de Cotopaxi al periodo 1 de enero al 31 de diciembre 2012 - Velasco Olalla, Beatriz Yolanda (2015)
The integral audit is a tool that he contributes of effective form, Allowing to evaluate the procedures of a company and detect new offers to improve raising policies, aims and procedures that couple is considered to be necessary to achieve the awaited results. The aplication of the Integral Audit in the company Sanbel Flowers Cia.Ltda. It is, with the aim to verify if there are fulfilled the established procedures and the performance of the activities. To develop this study investigation I use the royal information directly provided with the whole personnel and civil servants that it works in the company, Thank you the collaboration and by means of to the application of the methods investigations: The interview to the general manager, The surveys realized to the clerical staff and to the workers, As well as also the direct observation….